Komunikasi Penyuluh Pertanian Dalam Pemanfaatan Pompanisasi Di Desa Sungai Dua Kabupaten Banyuasin - Muhammad Andri Zuliansyah; Acip Rakhmat; Adli Adli; Nia Meitisari (Program Studi Agribisnis, Fakultas Pertanian, Universitas Singaperbangsa Karawang, 2023)
Communication is very important between agricultural extension workers and farmers to provide information or solve problems in cultivating swampland. The research objective was to identify the communication process of agricultural extension workers in the utilization of pompanization. The research method used a qualitative method with a descriptive approach. The research location was purposive in Sungai Dua Village, Banyuasin Regency, which consisted of key informants and supporting informants. Data collection techniques used observation, interviews and documentation. Data analysis used the Miles and Huberman model, namely reducing data, presenting data and drawing conclusions. Data validity test using source triangulation. The results showed that communicators from agricultural extension workers and communicants from combined farmer groups and farmer groups. The message conveyed by the agricultural extension workers regarding the use of pompanization in rice farming. Communication channels used are direct (interpersonal communication) and group (group communication). Communication effects in the delivery of agricultural extension workers information include cognitive effects, affective effects, and conative effects.